Über Almen - zwischen Agrikultur & Trashkultur - Kirchengast, Christoph (alpine space - man and environment, 2008)
The book "Über Almen, zwischen Agrikultur & Trashkultur" (About Alpine Pastures: agriculture and trash-culture) leads the reader from agricultural use of alpine meadows to touristic use and further to romanticistic views by urban societies. External views of alpine agriculture culminate in a complete virtualization of the term "Alm" (i.e. alpine pasture). This sociological study focuses on the view of Alpine peasants and how they cope with modern challenges.